Using Music Technology Creatively to Enrich Later-Life: A Literature Review - Creech, Andrea (Frontiers in Psychology, 2019)
Background: A growing body of evidence has demonstrated significant social and emotional benefits of music-making amongst senior citizens. However, several as-yet unresolved age-related barriers to ‘musicking’ have been identified. Positioned within the emergent field of gerontechnology, concerned with the interface between aging and technology research, this review of literature thus explores the potential for music technologies to function as a vehicle for creative musical opportunities in later-life. Methods: ERIC, PsychInfo and Web of Science databases were searched, focusing on the intersection between music, technology and ageing. The criteria for inclusion were that the paper should: 1) be in English; 2) report empirical research involving the use of music technologies intended to support receptive (listening, interpreting, reflecting) or active (playing, creating, performing) engagement with music amongst older persons, defined as being aged 60 years or above (United Nations, 2017); 3) be published as a peer reviewed journal article. Results: Of 144 papers screened, eighteen papers were retained. Ten studies focused on using technology to support musicking in the form of listening, reflecting and interpreting. Just five studies explored the utility of technology in promoting singing or playing instruments, while a further three were focused on music and movement. Conclusions: Overall, the literature reviewed suggests that older people, even those with complex needs, are capable of, and interested in using music technologies to access and create personally meaningful music. The limited research that does exist points to multiple and significant benefits that may be derived from receptive or active musicking supported by a range of music technologies.